4 - Cross-Border Education as Trade: Issues for Consultation, Policy Review and Research*: Jane Knight - Jane Knight, (Journal of Higher Education in Africa, 2004)
This paper is abridged from a report prepared for the African Association of Universities Workshop on GATS and Higher Education (May 2004) and includes information from papers written by the author for the Observatory of Borderless Higher Education and for UNESCO. This paper provides background information and an analytical framework to study the implications of cross-border provision of higher education in Africa—especially in the context of an increased emphasis on commercial provision and the existence of the General Agreement on Trade in Services (GATS). The major principles related to GATS rules for trade in education services are addressed and a summary of GATS commitments made by African countries to higher education is provided. A discussion of rationales and risks associated to the commercial import and export of education leads to an examination of potential policy implications related to increased cross-border mobility of higher education institutions/providers, programmes and student/scholars. Finally, key questions and issues are identified upon which education leaders and stakeholders may reflect for their relevance to the African context and the need for further research, policy review and consultation.